Media Ruins Cambodian Postwar Media Reconstruction and the Geopolitics of Technology - Jack, Margaret (Labor and Technology, 2023)
How a generation of tech-savvy young Cambodians is restoring historical media artifacts from before the war-and, in the process, helping to repair the Khmer Rouge's cultural destruction.During the Khmer Rouge regime (1975-1979), an estimated quarter to a third of the Cambodian population perished from execution, starvation, or disease. The regime especially targeted artists and intellectuals and their work, including films, photographs, and audio recordings. In Media Ruins, Margaret Jackcharts the critical role of media in the historical political landscape of Cambodia as well as in its post-conflict reconstruction and reconciliation. Along the way, Jack tells the remarkable stories of resourceful Cambodians in the decades that followed the end of the regime-those who worked to reconstruct their country's media infrastructure and restore their damaged cultural heritage.Jack describes the crucial role that media has played in helping the nation grapple with the traumas of its past and imagine brighter futures. She explores how tech-savvy Cambodian media creators have engaged in practices of infrastructural restitution-work that is both emotionally cathartic and politically vital. She also examines the ways these media creators have used digital tools to restore and disseminate lost media artifacts, while embracing an aesthetic of material decay as a visible reminder of loss. As these creators reconcile with the past, they are also finding ways to navigate the country's increasingly authoritarian media landscape. Bringing media and technology studies into conversation with trauma and memory studies, the book provides a unique, and necessary, perspective on post-conflict reconstruction.